Kinetic assessment of Ni-based catalysts in low-temperature methane/biogas steam reforming. (15th October 2016) - Turchetti, L.; Murmura, M.A.; Monteleone, G.; Giaconia, A.; Lemonidou, A.A.; Angeli, S.D.; Palma, V.; Ruocco, C.; Annesini, M.C.
Abstract: The reaction rate of low-temperature steam reforming was studied over two Ni-based catalysts. Experimental tests were carried out for temperatures between 400 and 550 °C and pressures between 1 and 7 bar, using methane and simulated biogas (1:1 methane-carbon dioxide mixture) as carbonaceous feed. The results were analyzed with a simplified reaction rate expression. The parameters of such expression were optimized in order to provide a tool for the design of an industrial scale reactor using the catalysts considered. Highlights: Two Ni-based catalysts are tested for steam reforming of methane and simulated biogas. Temperatures in the range 400–550 °C and pressures in the range 1–7 bar are considered. The catalysts show good activity in the experimental range considered. A rate equation was obtained for each catalyst based on a literature model.